Cytologic assessment of thyroid nodules - Updates in 2023 Bethesda reporting system, diagnostic challenges and pitfalls - Xiaobing Jin; Xin Jing (Elsevier, 2024)
This review summarizes changes and updates in the most recently published 2023 Bethesda System for Thyroid Cytopathology (TBSRTC). Further, the review focuses on challenges and pitfalls encountered in cytologic assessment of thyroid fine needle aspiration (FNA) specimens, with an emphasis on atypia of undetermined significance (TBSRTC category III) and the impact on risk of malignancy (ROM) among TBSRTC diagnostic categories following implementation of the terminology noninvasive follicular neoplasm with papillary-like nuclear features (NIFTP). The role of molecular testing as an adjunct to FNA cytology will be discussed.